2019
DOI: 10.1080/19768354.2019.1651766
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous leptin promotes autophagy in EBSS-induced PFCs

Abstract: Leptin is an important adipokine and plays a vital role in animals. However, the role of leptin in the autophagic response of pig fibroblast cells (PFCs) has not been fully elucidated. In this study, we investigated the relationship between leptin and autophagy as well as underlying molecular basis. We found that PFCs treated with EBSS could secrete leptin, and the leptin concentration in the supernatant of leptin transgenic PFCs was higher than that of WT PFCs. We found an increase in LC3-II protein level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Moreover, the LC3 II/LC3 I ratios were unaffected up to 4 h after cells were treated with RSL3 and erastin (Figures 1D and S1C ). Immunofluorescence (IF) revealed that autophagosomes were induced in HepG2 cells incubated with EBSS, which triggers autophagy, 27 and such effects were blocked by Wort, an autophagy inhibitor (Figure S1D,E ). However, no significant enhancement of autophagosome formation was observed in parallel with the increase of RB1CC1 in HepG2 cells treated with RSL3 and erastin (Figure S1D,E ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the LC3 II/LC3 I ratios were unaffected up to 4 h after cells were treated with RSL3 and erastin (Figures 1D and S1C ). Immunofluorescence (IF) revealed that autophagosomes were induced in HepG2 cells incubated with EBSS, which triggers autophagy, 27 and such effects were blocked by Wort, an autophagy inhibitor (Figure S1D,E ). However, no significant enhancement of autophagosome formation was observed in parallel with the increase of RB1CC1 in HepG2 cells treated with RSL3 and erastin (Figure S1D,E ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that hypoxia could lead to placenta leptin gene expression and production [48], and abnormal placenta leptin level was associated with aberrant trophoblast proliferation or invasion, as well as endothelial dysfunction, hypertension and fetal growth restriction [49,50], which may lead to PE. The interacting relations between leptin and autophagy varies in a tissue-specific pattern [51]. Although, the evidence in placenta is scarce, it was reported that autophagy was active in the placenta of PE women and leptin could modulate autophagy in various tissue types [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin-and starvation-induced autophagy are two different processes with common mechanisms [39][40][41]. Therefore, we used both autophagy induction methods to demonstrate the regulatory role of TGF-β1 under different autophagic conditions.…”
Section: Discussionmentioning
confidence: 99%